Evaluation and optimisation of physical activity in individuals with chronic obstructive pulmonary disease (COPD) - Ng, Li Whye Cindy (Curtin University, 2014)
The studies in this thesis evaluated the physical activity (PA) in individuals with chronic obstructive pulmonary disease (COPD), identified strategies to optimise PA, determined the effects of a supervised walking training program on performance during the endurance shuttle walk test (ESWT) and determined the minimal detectable difference for the ESWT.The measurement techniques used included: PA using motion sensors; HRQoL assessment; Fear of Falling Questionnaire, Hospital Anxiety and Depression Scale; and functional exercise testing.